Role of Defense Controlling Stability of a Prey-Predator Model with Disease in Predator Species - Das, Krishna Pada; Saha, Satyajit; Kumar, Rakesh (Discontinuity, Nonlinearity, and Complexity, 2026)
Defensive behavior is an important factor in changing the system dynamics. Particularly inducible defense in one population may help to persist that population in ecosystem.In this study we analyze a standard model of prey-predator interaction in presence of defensive properties in prey population and also consider the disease infection in predator population.We study local stability, bifurcation of the system around the equilibria and also derive ecological and disease basic reproduction number.The main aim of this work is to study the consequence of the defensive behavior on the model system in presence of disease in predator.Our findings show that defensive behavior in one population stabilizing the infected system contradicting the previous result suggesting destabilizing effect of disease infection.We have done extensive numerical studies to conclude that increasing defensive behavior actually stabilizing the system more rapidly.